Case report: ZEB1 expression in three cases of hepatic carcinosarcoma - Zhang, Mingming; Yang, Dongchang; Li, Lu; Liu, Lin; Wang, Ting; Liu, Tao; Li, Lei; Liu, Yanrong (Frontiers in Oncology, 2022)
Hepatic carcinosarcoma (HCS) is defined as a tumor that contains cancer from the epithelium and sarcoma from mesenchymal tissue. HCS has a low incidence rate and is composed of osteosarcoma, chondrosarcoma, or angiosarcoma. Though surgery is the main treatment for HCS, it has proven unsatisfactory, resulting in a very poor prognosis of HCS. Currently, the reports on HCS are mainly about the description of clinical pathological phenomena, imaging features, and mutation sites of related genes, the underlying molecular mechanism of HCS remains undefined. Through the dynamic process of epithelial-mesenchymal transition (EMT), cancer cells acquire a mesenchymal phenotype, simultaneously losing epithelial properties. Zinc finger E-box binding homeobox 1 (ZEB1) is an EMT-inducing transcription factor; its main regulatory target is E-cadherin in EMT process. Esophageal carcinosarcoma (ECS) is associated with EMT. The current study showed that EMT might promote the development of ECS and uterine carcinosarcoma (UCS), and ZEB1 was highly expressed in the sarcomatous components. In the current study, three cases were collected, and the clinicopathological features were compared with those of corresponding cases. The expression level, and subcellular localization of ZEB1 were detected using immunohistochemistry. The expression of the ZEB1 in the nucleus was found to be significantly higher in sarcomatous components than that in cancer components in all three cases, suggesting an association of HCS with EMT.